Ovarian Dynamics and Blood Flow Indices during Estrus in Purnathadi Buffaloes - Kathe, Aboli; Ingawale, Maheshkumar Vitthalarao; Deshmukh, Shyam Ganesh; Pawshe, Chaitanya Hemednrakumar; Hajare, Sunil Wasudeo; Ingole, Ranjit Suresh (The Indian Journal of Animal Reproduction, 2023)
The research work was implemented to study the ovarian dynamics and ovarian arterial blood flow by pulse-wave Doppler form with color Doppler ultrasonography during estrus in Purnathadi buffaloes. The mean ovarian diameter of left and right ovary was 2.27±0.08 and 2.37 ± 0.12 cm of right ovary and mean pre-ovulatory follicle diameter was 1.22 cm during estrus Purnathadi buffaloes. The mean ovarian pulsatility index and resistance index was 1.45 and 0.75 during estrus. The mean ipsilateral (on the side of pre-ovulatory follicle) and contralateral ovarian artery pulsatility index during estrus was 1.63±0.02 and 1.62±0.02. The mean ipsilateral (on the side of pre-ovulatory follicle) and contralateral ovarian artery resistance index during estrus was 0.77±0.01 and 0.75±0.01 respectively. The ovarian artery indices show non significant levels irrespective of presence of pre-ovulatory follicle.
Keywords: Buffalo; Ovarian artery; Preovulatory follicle; Ovarian dynamics